Business to business marketing - Vitale, Robert P.
Designed to prepare upper-level undergraduate and graduate business students for work in the exciting field of marketing, this text focuses on the basic principles of business marketing. Enlivened by interesting scenarios involving actual companies, people, and events within the business world, the examples serve to deepen student appreciation for business-to-business marketing while differentiating it from consumer marketing. A variety of real-world examples, based upon the authors' experience as business marketers in Silicon Valley, help to enrich the text